Equity valuation : Beiersdorf AG - Berninghaus, Max Georg Franz (2020)
This dissertation aims to determine the target price of Beiersdorf AG, a leading player in the personal care and self-adhesives market, to issue a buy, hold or sell recommendation relative to the market price. Thus, the underlying research question is: “What is Beiersdorf’s fair value per share at the 01st of January 2019 and resulting upside or downside potential for investors?”. The valuation for German DAX listed Beiersdorf is based on a profound company, competitor and market analysis, including past development and future outlook of Beiersdorf’s financials and market trends in the consumer goods and adhesives industry. The valuation techniques comprise the WACC DCF-method as representative for the intrinsic valuation and is complemented by a relative valuation, using trading forward-multiples. The valuation results in a target price range of EUR 94.40 to 97.84 per share. Compared with a closing price of EUR 91.16 per share on Friday, the 28th of December 2019 (last trading day in 2018), a hold recommendation can be addressed due the marginal deviation of only +3.6 percent to +7.3 percent. Furthermore, the hold recommendation is in line with the equity research of Credit Suisse.